(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2024)
The socio-political frameworks of literary theory play a significant role in analyzing and interpreting contemporary literature, as they enable a deeper understanding of the complex social and political issues present in modern texts. Theories such as Marxism, feminism, and postcolonialism provide critical perspectives that highlight the ways literature reflects, critiques, and sometimes challenges societal structures and power dynamics. By applying these frameworks, readers can explore how authors address themes of identity, oppression, resistance, and globalization within their works. This approach also allows for a nuanced exploration of how diverse voices and marginalized perspectives are represented in contemporary narratives. Ultimately, socio-political literary theories offer valuable tools for uncovering layers of meaning, encouraging readers to engage critically with literature as a form of social commentary and cultural expression.